Association between parity and fistula location in women with obstetric fistula: a multivariate regression analysis. (8th February 2016) - Sih, AM; Kopp, DM; Tang, JH; Rosenberg, NE; Chipungu, E; Harfouche, M; Moyo, M; Mwale, M; Wilkinson, JP
Abstract : Objective: To compare primiparous and multiparous women who develop obstetric fistula (OF) and to assess predictors of fistula location. Design: Cross‐sectional study. Setting: Fistula Care Centre at Bwaila Hospital, Lilongwe, Malawi. Population: Women with OF who presented between September 2011 and July 2014 with a complete obstetric history were eligible for the study. Methods: Women with OF were surveyed for their obstetric history. Women were classified as multiparous if prior vaginal or caesarean delivery was reported. The location of the fistula was determined at operation: OF involving the urethra, bladder neck, and midvagina were classified as low; OF involving the vaginal apex, cervix, uterus, and ureters were classified as high. Main outcome measures: Demographic information was compared between primiparous and multiparous women using chi‐squared and Mann–Whitney U‐tests. Multivariate logistic regression models were implemented to assess the relationship between variables of interest and fistula location. Results: During the study period, 533 women presented for repair, of which 452 (84.8%) were included in the analysis. The majority (56.6%) were multiparous when the fistula formed. Multiparous women were more likely to have laboured <1 day (62.4 versus 44.5%, P < 0.001), delivered a live‐born infant (26.8 versus 17.9%, P = 0.026), and have a high fistula location (37.5 versus 11.2%, P < 0.001). Multiparity [adjusted odds ratio (aOR) = 4.55, 95% confidence interval (CI) 2.27–9.12)] and history of caesarean delivery (aOR = 4.11, 95% CI 2.45–6.89) were associated with development of a high fistula. Conclusions: Multiparity was common in our cohort, and these women were more likely to have a high fistula. Additional research is needed to understand the aetiology of high fistula including potential iatrogenic causes. Tweetable abstract: Multiparity and caesarean delivery were associated with a high tract fistula in our Malawian cohort. Tweetable abstract: Multiparity and caesarean delivery were associated with a high tract fistula in our Malawian cohort. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights13901